Clinical Integration in a Dental School Clinic Through an Enhanced Patient Intake Process. Issue 9 (1st September 2019) - Robinson, Fonda G.; Fischbach, Henry; Salisbury, Jessica; Stefanik, Dawne; Kearney, Rachel; Fields, Henry W.
Abstract : Dental care in the U.S. is based on a general practice model of care delivery that can be enhanced by the integration of the dentists and allied dental professionals. There are 25 U.S. dental schools with associated dental hygiene programs, presenting distinctive opportunities for educating the dental health care team. Integrated educational clinical experiences are believed to positively influence teamwork and quality of care that parallels the authentic general practice environment. Lean management, developed by Toyota and used in a variety of types of organizations including health care, provides a distinctive blend of engineering principles and operations management to enhance business and operations processes. A fundamental principle of Lean management is the elimination of waste and preservation of only those value‐added components of a process. The faculty and staff of The Ohio State University College of Dentistry, trained in Lean process improvement, applied techniques to enhance and integrate an inefficient patient intake (admissions) process. The aim of this initiative was to improve patient throughput in the patient intake process and to provide dental and dental hygiene students with enhanced educational experiences from improved clinical integration. These goals were achieved through streamlining patient flow and relocating major phases of the process. Although new patient retention and cancellation/no‐show rates remained mostly unchanged, this enhancement project resulted in improved access to care, improved continuity of care, expanded scope of dental services offered, improved patient satisfaction, and enhanced dental and dental hygiene student collaboration and teamwork. These outcomes suggest that process improvement initiatives can serve as valuable opportunities for integration of the dental health care team.